A Feasibility Study on Setting Up an Electroplating Facility for Plastics (Allied Electroplating Services) - Rendon, Elsa D. (College of Engineering, 1995)
Since plastics are light, strong, durable, well suited for mass production techniques and corrosion resistant, they are now widely being electroplated. The plated plastics are used in the automobile for interior trim, handles and bezels and for certain items of exterior trim including front grilles and lamp bezels. Domestic appliances, plumbing ware, toys, bicycles, furniture and tools all use electroplated plastics; millions of plated plastic knobs, handles and switched are used every year on radio, television and hi-fi equipment. The fashion trade uses plated plastics to produce buttons and imitation costume jewelry. The study has relied mainly on secondary data and review of relevant literature during the course of the study. Some agencies, where numerous materials were available, were used to aid the study in investigating the workability of the proposed plastics electroplating shop. These include the Center for Research and Communication (CRC), the Department of Trade and Industry (DTI), the National Statistical Office (NSO), the Metals Industry Research and Development Center (MIRDC), the Technology and Livelihood Research Center (TLRC), and the Board of Investments (BOI). In the Market analysis conducted, it was determined that there are three local firms that cater to plating-on-plastics (POP). However, considering only the Automotive and Appliance sectors, these three firms captured 32% and 45%, respectively. Therefore, there is an available 68% and 52% of these two sectors, which can still be captured. The analysis provided encouraging results in that the demand for POP products is projected to increase for the years 1996 to 2000. In the technical analysis, the group decided to concentrate on the Automotive sector, since the products requiring electroplating were basically standard. The technology required to electroplate plastics is simple, yet effective; strict quality is maintained throughout the entire process. Based on sales and production cost estimates, the projected cash flows and income statements for the coming years (1996 to 2000) showed that the company can make it, amidst the competition.